Video Promosi Agen46 BNI Wilayah Padang Dalam Bentuk Drama Musikal - Muhammad Wahyudi; Arius Medi (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This study employs promotional videos as a strategic tool for shaping personal and corporate identity. Focused on Agen46 BNI, the design objective is to create a compelling promotional medium leveraging the musical drama concept to heighten public awareness and educate the audience on the benefits of Agen46 BNI. Utilizing the 4-D method (Define, Design, Develop, Disseminate), and employing the 5W+1H data analysis method, the design process ensures alignment with specific campaign needs. The resulting promotional video for Agen46 BNI in the Padang Region takes the form of a musical drama, progressing through creative stages of pre-production, production, and post-production. The primary outcome is a promotional video, serving as the main media. To amplify its impact, supporting media such as t-shirts, calendars, posters, notebooks, QRIS stands, and X-banners. This strategy aims to not only enhance public awareness but also educate the audience on the distinct benefits of Agen46 BNI, establishing a comprehensive and engaging promotional campaign.